Transient Canonical Wnt Stimulation Enriches Human Bone Marrow Mononuclear Cell Isolates for Osteoprogenitors. (17th November 2015) - Janeczek, Agnieszka A.; Tare, Rahul S.; Scarpa, Edoardo; Moreno-Jimenez, Ines; Rowland, Caroline A.; Jenner, Dominic; Newman, Tracey A.; Oreffo, Richard O. C.; Evans, Nicholas D.
Abstract: Activation of the canonical Wnt signaling pathway is an attractive anabolic therapeutic strategy for bone. Emerging data suggest that activation of the Wnt signaling pathway promotes bone mineral accrual in osteoporotic patients. The effect of Wnt stimulation in fracture healing is less clear as Wnt signaling has both stimulatory and inhibitory effects on osteogenesis. Here, we tested the hypothesis that transient Wnt stimulation promotes the expansion and osteogenesis of a Wnt-responsive stem cell population present in human bone marrow. Bone marrow mononuclear cells (BMMNCs) were isolated from patients undergoing hip arthroplasty and exposed to Wnt3A protein. The effect of Wnt pathway stimulation was determined by measuring the frequency of stem cells within the BMMNC populations by fluorescence-activated cell sorting and colony forming unit fibroblast (CFU-F) assays, before determining their osteogenic capacity in in vitro differentiation experiments. We found that putative skeletal stem cells in BMMNC isolates exhibited elevated Wnt pathway activity compared with the population as whole. Wnt stimulation resulted in an increase in the frequency of skeletal stem cells marked by the STRO-1 bright /Glycophorin A − phenotype. Osteogenesis was elevated in stromal cell populations arising from BMMNCs transiently stimulated by Wnt3A protein, but sustained stimulation inhibited osteogenesis in a concentration-dependent manner. These results demonstrate that Wnt stimulation could be used as a therapeutic approach by transient targeting of stem cell populations during early fracture healing, but that inappropriate stimulation may prevent osteogenesis. Video Highlight: https://youtu.be/Wcs-crLvXbQ Abstract : Therapeutic approaches to modulate Wnt signaling in fracture healing should consider the complexity of Wnt signaling requirements for successful differentiation of osteoblasts from progenitors present at injury sites. Transient exposure of fresh bone marrow cells to a canonical Wnt stimulus increases CFU-O potential and osteogenic differentiation of stem/progenitor cell populations.